COMPARATIVE STUDY OF NATURAL AND ARTIFICIAL VEGETATIVE GROWTH IN PLANTS - Lisa Arianti; Nurul Hasanah (JURNAL ILMIAH NUSANTARA, 2025)
When a plant reproduces asexually, the parts of the parent plant that can grow are removed and become separate new plants. This research used a qualitative method. The study was conducted in Hamlet V Bukit Lalang, located in Pasiran Village, Langkat Regency. The results showed that during grafting, no visible changes were observed in the first two weeks after the process. In the first two weeks after cutting, no changes occurred. In the first week after grafting, no changes were observed. Bending, when the branches bend downward, no changes occurred in the first two weeks. In the first week after planting, called the scion phase, no changes were observed. Growth changes were observed in the following week.